Sistem Maklumat Akademik UUM - Ruzelan, Khalid (2002)

(untitled)
Academic and Student Imformation (ASIS) was developed by Pusat Komputer in 1998 to help lecturers and Jabatan Hal Ehwal Akademik Universiti Utara Malaysla to process students' results. The purpose of this research is to develop a system that can be used together with ASIS to manage courses more systematically and to perform statistical analysis on the considered data. The system enables lecturers to create a workspace to input and edit assignments, quizzes, tests and final examination scores. The number of fields to store students' performance such as assignments, tests etc will be determined by the lecturer and the system will calculate automatically the contribution of each set of the data to the total coursework score and final score depending on the percentage specified. The list of students registered for the course will directly be retrieved from ASIS. Coursework and final examination score will be transferred online to ASIS at the end of semester. Besides that, it is noticed that ASIS database contains a lot of data that can be utilised to assist System Penasihatan Pelajar. Graphical user interfaces (GUI) of the system will be developed using Visual Basic meanwhile data will be processed by SAS.